The Effects of Training, Motivation, and Creativity on Employee Performance - Qowiyyudin, Muhammad; Nirawati, Lia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze and identify the influence of training, motivation, and creativity on employee performance at PT Sinergi Gula Nusantara PG Lestari. This study uses a quantitative approach with an associative method, which is designed to test the causal relationship between independent and dependent variables. The variables of training, motivation, and creativity are hypothesized to have an influence on shaping employee performance. Data were obtained by distributing questionnaires to 50 respondents who are employees of PT Sinergi Gula Nusantara PG Lestari. Data analysis was carried out using SPSS, involving validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, simultaneous test (F test), partial test (t test), and coefficient of determination. The results of the study indicate that simultaneously the variables of training, motivation, and creativity have a significant effect on employee performance. Partially, the variables of training, motivation, and creativity have a significant effect on employee performance.